The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/1348-0421.12534
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, characterization and expression of immunoglobulin D on pathogen challenge and pathogen associated molecular patterns stimulation in freshwater carp, Catla catla

Abstract: The primordial immunoglobulin class, IgD, was the first non-IgM isotype discovered in teleosts. The crucial roles of IgM and IgZ in imparting systemic and mucosal immunity, respectively, in various fish species have been widely established. However, the putative function of a unique IgD isotype during pathogenic invasions has not been well explored. The present study reports the existence of an IgD ortholog in freshwater carp, Catla catla, and further evaluates its differential expression profile in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Although, SVCV primarily affects fishes of the Cyprinidae family (Ahne et al, 2002) but VHSV infects a variety of fish species belonging to various families (Al-Hussinee et al, 2011). To investigate the response of caspase-8 gene in rhabdovirus infections, rohu fingerlings were injected with an inactivated rhabdovirus vaccine of animals containing RNA viral genome (Basu et al, 2016;Banerjee et al, 2017). The result showed significant (p < 0.05) increase in caspase-8 gene expression in all tested organs, and the most significant induction was noted in the spleen at 72 h post-injection.…”
Section: Discussionmentioning
confidence: 99%
“…Although, SVCV primarily affects fishes of the Cyprinidae family (Ahne et al, 2002) but VHSV infects a variety of fish species belonging to various families (Al-Hussinee et al, 2011). To investigate the response of caspase-8 gene in rhabdovirus infections, rohu fingerlings were injected with an inactivated rhabdovirus vaccine of animals containing RNA viral genome (Basu et al, 2016;Banerjee et al, 2017). The result showed significant (p < 0.05) increase in caspase-8 gene expression in all tested organs, and the most significant induction was noted in the spleen at 72 h post-injection.…”
Section: Discussionmentioning
confidence: 99%
“…SVCV primarily affects cyprinid fishes (Ahne et al 2002) but the host range of VHSV is very wide (Al-Hussinee et al 2011). To understand the response of Caspase-9 in rhabdoviral infections, inactivated rhabdoviral vaccines of animals were injected into rohu fingerlings (Basu et al 2016;Banerjee et al 2017) and the data revealed significant increase in caspase-9 gene expression in gill, liver and spleen. In large yellow croaker, caspase-9 gene expression was also induced in spleen and kidney following poly I:C or bacterial vaccine stimulation, and it was highest at 48 h and then decreased at 72 h (Mu et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Healthy fish were parted into two groups: control and challenged. Challenged group was infected with Aeromonas hydrophila (ATCC 35654) and Streptococcus uberis (ATCC 700407) as described by Banerjee et al . The control fish were injected with 100 µl of phosphate buffer saline (PBS) maintained in the other tank.…”
Section: Methodsmentioning
confidence: 99%
“…Challenged group was infected with Aeromonas hydrophila (ATCC 35654) and Streptococcus uberis (ATCC 700407) as described by Banerjee et al. 28 The control fish were injected with 100 µl of phosphate buffer saline (PBS) maintained in the other tank. After 24, 48 and 72 hr, the challenged fish along with control group were anesthetized using tricane methane sulphonate (Sigma-Aldrich, USA) and sacrificed for isolating the immunologically significant tissues such as liver, spleen, intestine, kidney, gill, skin and blood.…”
Section: Pathogenic Challenge and Tissue Samplingmentioning
confidence: 99%